Modulation of essential fatty acid levels in coconut oil with flaxseed oil - A.A. Joshi; M.V. Hegde; A.A. Zanwar (Grasas y Aceites, 2023)
Coconut oil (CO) is a popular cooking medium but its lack of essential fatty acids (FA) is a health concern. Therefore, the aim of this work was to improve the FA profile of CO by blending with flaxseed oil (FO). Blends with various percentages of FO were prepared and studied for physicochemical characterization, thermal and long-term storage stability. The results indicated that the blends made favorable alterations in FA composition without adverse effects to the oxidative stability of the fatty acids and they resisted secondary thermal deterioration up to two hours at 180 ºC. The blend with the highest percentage of FO was stable for nine months. THP-1 cell line studies showed that ω-3 FA from the blend was incorporated into the cells with no adverse effect on cell viability but the inflammatory markers studied remained unaltered. Thus, CO and FO blends could be stored for at least nine months and could be used as cooking medium when prolonged heating is not involved.